PENERAPAN MODEL TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 7 PIDIE - Nufiar (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
This study aims to determine how the application of the Talking Stick model can improve the learning outcomes of 4th grade students of MIN 7 Pidie. This type of research is Classroom Action Research (CAR) with the research subjects being 24 of the 4th grade students of MIN 7 Pidie. The data collection techniques used are observation, interviews, documentation and tests. The application is carried out by using a stick used as a medium to determine students' turns to answer questions or express opinions. Students who hold the stick are responsible for providing answers, while other students listen and provide responses if necessary. From the results of the study, it was found that in cycle I the average value obtained by students was 59.37 and the classical completeness obtained by students was 33.33%. In cycle II the average value obtained by students was 88.08 and the classical completeness obtained by students was 100%. Thus, it can be concluded that the application of the Talking model can improve the learning outcomes of fourth-grade students of MIN 7 Pidie.